PENERAPAN MOTIF NUSANTARA DALAM PENCIPTAAN KARYA BATIK DI CV. TARUM BALI SEJAHTERA - Nurlaeli Dwi Safitri; Ni Kadek Karuni; Ida Ayu Gede Artayani (Hastagina : Jurnal Kriya Seni, 2022)
Internship / work practice is a practical activity for students with the aim of gaining experience from these activities, which can later be used as a professional development for students. This activity is carried out directly in the world of work for real. As for this internship activity the creator does on the CV. Tarum Bali Sejahtera in Gianyar Bali.This place of business is dabbling in textiles, especially batik and natural coloring. The method of creation used in the creation of the work of this apprenticeship process is through two approaches intuitively, and through carefully planned, analytical and systematic scientific methods. In the method refers to the theory of creation proposed by SP. Gustami in his book entitled "The process of craft art creation: methodological strands" explains the process of creating craft works through three pillars of creation such as exploration, experimentation, and formation of Gustami, 2004: 31 (in Kusyati, 2019:22). The concept of creating this work is to make a work in the form of batik which is the result of collaboration between batik tulis with canting, as well as brushes as additional decorations in the making of batik works. The process of creating batik writing works is done through the design stage, namely digging up the idea that will be created next is the manufacturing process that is through the steps of making motifs, copying motifs on fabric, cutting, coloring, locking and roding. This work is in the form of batik with typical balinese bondowoso coffee motifs, kawung and machete motifs of central Java, slopes of West Java, kakul - kakulan, Samblung patra and balinese poleng fabric, Shaho khas Balikpapan and the addition of motifs in the form of truntum, cecek 5, ceccek 7, ukel sawut and ukel - ukelan. Coloring uses natural colors with a fixation in the form of tunjung and alum.